Odpowiedzi

2010-02-27T20:28:44+01:00
Dane jest wyrażenie W(x) = x³-2x²-3x
x⁶-18x⁴+81x²


a) x∈R/{-3,0,3}
b)
x³-2x²-3x
W(x) =--------------- =
x⁶-18x⁴+81x²
(x+1)(x-3)
=----------------=
x(x²-9)²
x+1
=----------------
x(x²-9)(x+3)
  • Użytkownik Zadane
2010-02-27T20:30:28+01:00
X⁶-18x⁴+81x²≠0
x²(x⁴-18x²+81)≠0
dajemy niewiadomą pomocniczą t=x²
t(t²-18t+81)≠0
t(t-9)²≠0 (wzór skróconego mnożenia)
t≠0 t≠9
ale t=x², więc x≠0 x≠3 x≠-3
D=R\{-3;0;3}

skracanie:

x³-2x²-3x = x(x²-2x-3) = x(x+1)(x-3)
x⁶-18x⁴+81x² = x²(x-3)(x+3) = x²(x-3)(x+3)

x(x-3) się skraca:

(x+1)
x(x+3)
1 5 1